2014
DOI: 10.1007/s00521-014-1662-5
|View full text |Cite
|
Sign up to set email alerts
|

New results on the stability of fuzzy cellular neural networks with time-varying leakage delays

Abstract: In this paper, fuzzy cellular neural networks with time-varying delays in the leakage terms are studied. Without assuming the boundedness on the activation functions, some sufficient conditions for the existence, uniqueness and global exponential stability of equilibrium point are established by using the fixed point theorem and constructing suitable Lyapunov functional, which are new, and they improve previously known results. Moreover, an example is given to demonstrate the feasibility of our method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These models combined fuzzy operation (fuzzy AND and fuzzy OR) with cellular neural networks. Recently scholars have found that FCNNs are useful in image processing, optimization and control [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25]. The sufficient stability criteria have become one of research topic in these models.…”
Section: Introductionmentioning
confidence: 99%
“…These models combined fuzzy operation (fuzzy AND and fuzzy OR) with cellular neural networks. Recently scholars have found that FCNNs are useful in image processing, optimization and control [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25]. The sufficient stability criteria have become one of research topic in these models.…”
Section: Introductionmentioning
confidence: 99%
“…He and Chu [21] studied the stability of fuzzy cellular neural networks having time-varying delay in leakage term deprived of assuming the boundedness of activation function. Other related works readers can refer to [22]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of wide practical applications of CNNs explains the still growing interests of many researchers, the recent literatures on this subject which can be found in [3,13,14,23,[30][31][32][33]36]. Oscillation and instability of CNNs may be caused by the delay, the research of the dynamic properties for delayed neural network has been attracted broad attention by many authors, see e. g. [8,10,24,37,38]. In generally, the neural networks contain different types of time delays, such as constant delays, time-varying delays, finite(or infinite) delays and distributed delays.…”
Section: Introductionmentioning
confidence: 99%